THE RELATIONSHIP BETWEEN STUDENT PERCEPTIONS OF E-LEARNING AND THE LEARNING MOTIVATION LEVEL OF STUDENTS OF THE SOCIAL SCIENCE EDUCATION DEPARTMENT, UNIVERSITY OF LAMPUNG - Riyanto; Zulkarnain; Nugraheni, Irma Lusi (Journal Learning Geography, 2023)
This study aims to determine the relationship between perceptions of the e-learning method and the level of learning motivation of students of the Social Science Education Department, University of Lampung. This study used a quantitative approach using a quantitative survey research design and data analysis using the Stata program version 14.2.The results of this study idicate (53%) students of the Department of Social Sciences, University of Lampung have a curently perception of the e-learning method and (52%) low learning motivation. Based on the Simultaneous Test (F test) it was found that there was a relationship between students' perceptions of the e-learning method and the level of learning motivation of students in the Department of Social Science Education, University of Lampung with a Prob>F value of 0.0097. Because of that there is a significant relationship between students' perceptions of the e-learning method with the level of student motivation in the Department of Social Science Education, University of Lampung.